2020
DOI: 10.1177/1474885120932253
|View full text |Cite
|
Sign up to set email alerts
|

On the concept of political manipulation

Abstract: Much liberal-democratic thought has concerned itself primarily – even exclusively – with coercive interference in citizens’ lives. But political actors do things – they engage in influential speech, they offer incentives, they mislead other actors, they disrupt the expected functioning of decision-making mechanisms etc. – that fall short of coercion, yet may nonetheless call for normative evaluation and public justification, precisely because they serve to purposively alter citizens’ beliefs, intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…Finally, according to the theory (Blumenthal- Barby, 2012;Valenti & Giacco, 2022;Whitfield, 2022), there are several motivations for people's behavior; among them, we have (1) coercion (force or violence done to someone to force them to say or do something),…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, according to the theory (Blumenthal- Barby, 2012;Valenti & Giacco, 2022;Whitfield, 2022), there are several motivations for people's behavior; among them, we have (1) coercion (force or violence done to someone to force them to say or do something),…”
Section: Discussionmentioning
confidence: 99%
“…Finally, according to the theory (Blumenthal‐Barby, 2012; Valenti & Giacco, 2022; Whitfield, 2022), there are several motivations for people's behavior; among them, we have (1) coercion (force or violence done to someone to force them to say or do something), (2) convenience (favorable, opportune, or profitable state), and (3) conviction (ethics or politics to which one firmly adheres). In this sense, we can observe that in case 1, the company had a strong relationship with the communities; however, initially, it did not agree to participate in the solution to the contamination of the Chile River, but later, given the need to expand its operations, it agreed to build the wastewater treatment plant.…”
Section: Discussionmentioning
confidence: 99%
“…They found that political party dominance is often associated with high levels of corruption, due to a lack of accountability and transparency in political systems dominated by one party. Research conducted by (Whitfield, 2022) investigated the hegemony of political parties in several Eastern European countries after the fall of the communist regime. They show how political parties that dominated in the past still retained their influence after the transition to democracy, and how this influenced the process of democratic consolidation in the region.…”
Section: Political Party Hegemonymentioning
confidence: 99%
“…The attempts to produce an agreed upon definition, let alone theory, of manipulation have not been successful. People can manipulate in different ways, and therefore rather than seeing manipulation as a single phenomenon, it might be more pragmatic to distinguish between different ways of manipulating (Whitfield 2020). For example, manipulating people directly to believe or do something may be very different from manipulating information, which involves illicitly changing the meaning of information (Billig & Marinho 2014, 2017).…”
Section: Studying Statistical Manipulationmentioning
confidence: 99%
“…Recently, there has been an interest in the general processes of manipulation and also in the ways that politicians and others might use language to manipulate their audiences (for instance, Maillat & Oswald 2009, 2011; de Saussure 2013; Maillat 2013; Cabrejas-Peñuelas 2017; Whitfield 2020; Masia 2021). One point should be stressed at the outset of this article.…”
Section: Introductionmentioning
confidence: 99%